Art and architecture of thailand : from prehistoric times through the thirteenth century. - Woodward, Hiram (Brill, 2005)
The first ever comprehensive survey work on the art and architecture of Thailand from the earliest times until the establishment of the Thai-speaking kingdoms. A systematic and elucidating history of pre-fourteenth-century Thailand in a volume indispensable to historians of art, religion, politics, and society.